Standardizing postpartum family planning counseling guidance in Ghana: A stepped-wedge cluster randomized implementation effectiveness trial - Sarita Sonalkar; Ernest Maya; Chris Guure; Arden McAllister; Dzifa Puplampu; Roseline Doe; Robert Gallop; James Kiarie; Mary Eluned Gaffield (PLoS ONE, 2026)
Background Postpartum family planning can reduce morbidity and mortality for parents and children, however, up to 62% of birthing people have an unmet need for contraception due to implementation challenges. In this study, we aimed to evaluate implementation and effectiveness of the Postpartum Family Planning Package, a multifaceted implementation strategy combining provider use of the World Health Organization Medical Eligibility Criteria Mobile App (WHO MEC app), provider education, and counseling restructuring on the postnatal ward, to promote individualized family planning counseling prior to hospital discharge after childbirth. Methods We conducted a stepped-wedge trial in the Greater Accra and Eastern regions of Ghana. The Postpartum Family Planning Package implementation strategy was introduced sequentially at three public hospitals. We used a generalized linear mixed effects model to adjust for the time variable via the random effects part of the model, controlling for all other independent variables. Additionally, we assessed for time by intervention interaction. Results From 5 th October 2020–1 st October 2021, we enrolled 2096 patients and 191 providers. Post-intervention encounters were more likely to include discussion of all appropriate postpartum family planning methods compared to pre-intervention encounters (63% vs 39%). Patients counseled individually post-intervention were four times more likely to have all appropriate family planning methods discussed (aOR 4.28; 95% CI 2.35, 7.78). A family planning method decision was made before discharge in 49.5% of post-intervention encounters, compared to 18.3% pre-intervention (aOR 4.45; 95% CI 2.85, 6.93). Individual counseling was associated with higher uptake of family planning methods prior to discharge (aOR 1.74; 95% CI 1.04, 2.91). Conclusion Implementation of the Postpartum Family Planning Package resulted in high fidelity to the intervention and was effective in promoting patient decision to select contraceptive methods postpartum. Future research should examine the effect of our strategy when used during antenatal and all other postpartum encounters, as well as mechanisms to improve method uptake.